The Intervening Influence of Economic Growth on Fiscal Policy Stance and Public Expenditure in Kenya - Gatauwa, J. M.; Kaijage, E. S.; Sifunjo, K. Sifunjo; Nganga, T. W. Kiriti (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2018)
This paper investigates the intervening influence of economic growth on the relationship between fiscal policy stance and public expenditure in Kenya from 1964 to 2015 using a Vector Error Correction Model. The results indicate that economic growth has an intervening influence on the relationship between fiscal policy stance and public expenditure in Kenya. The findings further show that fiscal policy, economic growth and public expenditure are cointegrated using the Johansen test and the bound test but there is no short-run causality between the variables as indicated by the Wald test statistics. The findings suggest that economic growth explains the extent to which fiscal policy stance affects the level of public expenditure in Kenya even though fiscal policy stance has a negative relationship with public expenditure.